The Application of Water Cooling on Reducing NOx from a Gas Burner System - Mohd. Jaafar, Mohammad Nazri; Andrews, G. E.; MkPadi, M. C. (Universiti Putra Malaysia Press, 2005)
A gas burner system applying water cooling has been investigated using a 140mm inside diameter combustor of 294-mm length. The combustor was placed vertically upwards. All tests were conducted using natural gas only. A fixed straight blade radial swirler with 76-mm outlet diameter was placed at the inlet plane of the combustor. An orifice plate of 59 mm was inserted at the exit plane of the swirler to enhance turbulence and help in mixing of the fuel and air. Fuel was injected at the back plate of the swirler using central fuel injector with eight fuel holes pointed radially outward. Tests were conducted at 5mmH 20 pressure loss. A reduction of about 21.53% on NOx emissions was achieved at equivalence ratio of near stoichiometric (0.88) and a reduction of 35.7% was achieved at equivalence ratio of 0.42. Other emissions such as carbon monoxide were well under 100 ppm except below the equivalence ratio of 0.5 due to cooling effect. Unburned hydrocarbon emissions were well below 10 ppm except below the equivalence ratio of 0.5.